Derivatives Usage by Non-Financial Firms in Thailand; implications on the hedging strategy - Chawla, Veerathep (2007)
This dissertation is the result of the research carried out to investigate the derivatives usage in 65 non-financial companies across 8 specified industries in Thailand. The use of derivatives in Thailand is growing rapidly every year, our survey shows 75% of firms using derivatives in their hedging strategy. There is no significance in the use between Thai and Foreign companies in Thailand, while smaller firms do not use derivatives as much as larger firms, especially large listed companies. In addition, firms with more involvement in foreign business activities are more likely to use derivatives than firms with little to no foreign activities.